Enantioselective syntheses of (R)-pipecolic acid, (2R,3R)-3-hydroxypipecolic acid, beta-(+)-conhydrine and (-)-swainsonine using an aziridine derived common chiral synthon - Chavan, Subhash P.; Khairnar, Lalit B.; Pawar, Kailash P.; Chavan, Prakash N.; Kawale, Sanket A. (RSC Advances, 2015)
Concise total syntheses of (R)-pipecolic acid, (R)-ethyl-6-oxopipecolate, (2R, 3R)-3-hydroxypipecolic acid and formal syntheses of beta-(+)-conhydrine, (-)-lentiginosine, (-)-swainsonine and 1,2-di-epi-swainsonine have been accomplished starting from a common chiral synthon. The present strategy employs regioselective aziridine ring opening, Wittig olefination and RCM as the key chemical transformations.

Formal synthesis of brivaracetam: a key to construct the pyrrolidone scaffold using Pd-catalyzed oxidative cyclization and ring-closing metathesis reaction - Chavan, Subhash P.; Kawale, Sanket A.; Chavan, Prakash N. (Tetrahedron Letters, 2019)
A short and efficient synthetic approach for brivaracetam has been accomplished via two different routes which utilize Pd-catalyzed oxidative cyclization and ring-closing metathesis (RCM) as the key reaction. These two routes are novel, simple, scalable and rely on (E)-pent-2-en-1-ol and valeraldehyde as a commercially available starting material to yield brivaracetam with good overall yield. (C) 2019 Published by Elsevier Ltd.
Keywords: Antiepileptic drugs; Pd-catalyzed oxidative cyclization; pyrrolinone; Ring-closing metathesis reaction

Total synthesis of (+/-)-quinagolide: a potent D-2 receptor agonist for the treatment of hyperprolactinemia - Chavan, Subhash P.; Kadam, Appasaheb L.; Kawale, Sanket A. (ACS Omega, 2019)
A potent dopamine (D-2) receptor agonist (+/-)-quinagolide, which is used for the treatment of hyperprolactinemia, was synthesized using the ring closing metathesis (RCM) approach from meta-hydroxybenzaldehyde as the starting material. The key features of this synthesis are pyrolytic elimination, late-stage expedient synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates from olefin 6, via conjugate addition-elimination upon acetate 11, followed by RCM and phenyliodine bis(trifluoroacetate) (PIFA)-mediated Hofmann rearrangement of piperidine-3-carboxamide, which enables the synthesis of 3-aminopiperidine skeleton of quinagolide. For the total synthesis of natural products such as ergot alkaloids, late-stage synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates using RCM and PIFA-mediated Hofmann rearrangement of piperidine-3-carboxamide, which allows quick access to the synthetically challenging 3-aminopiperidine skeleton, are the main achievements of the present work.

Application of allylic amine formation from aziridine-2-ol under appel reaction condition: synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester - Chavan, Subhash P.; Kawale, Sanket A.; Patil, Niteen B.; Kalbhor, Dinesh B. (Tetrahedron Letters, 2021)
PPh3/I-2/imidazolde mediated allyl amine formation from aziridine-2-alcohol was explored for the synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester. (C) 2021 Published by Elsevier Ltd.
Keywords: Allyl amine; Aziridine-2-alcohol; Aziridinium ion; Birch reaction; Ring opening

Formal synthesis of (-)-quinagolide: diastereoselective ring expansion via a bicyclic aziridinium ion strategy to access the octahydrobenzo[g]quinoline architecture - Chavan, Subhash P.; Kawale, Sanket A.; Pisal, Mahesh M.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2021)
The diastereoselective formal synthesis of (-)-quinagolide, a D-2 receptor agonist, has been achieved. The synthesis started from L-pyroglutamic acid and relied on utilization of (a) a stereospecific catalytic hydrogenation and diastereoselective Horner-Emmons-Michael cascade to obtain functionalized prolinate, (b) a Lewis acid mediated Pummerer cyclization to construct a tricyclic fused ring system, and (c) a diastereoselective ring expansion via a bicyclic aziridinium intermediate to access the required 3-substituted piperidine scaffold.

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion